Edukasi tentang pernikahan dini dari perspektif psikososial, budaya dan kesehatan reproduksi - Chr. Argo Widiharto; Farikha Wahyu Lestari; Suhendri Suhendri (Altruis: Journal of Community Services, 2022)
There has been an increase in cases of early marriage nationwide during the Covid-19 pandemic. Based on data from the Central Java DP3AP2KB, there were 11,301 cases of early childhood marriages for girls and 1,671 for boys. This also happened in Semarang Regency, Central Java, which was caused by the decline in the economic level of the community so that marrying underage children was considered as an alternative problem solving. For this reason, it is necessary to have an early marriage prevention program in the form of changing people's mindsets, especially mothers and children, which also provide solutions to the problems of early marriage. The program that is run as an effort to prevent early marriage is the Early Marriage Community Partnership Program (PKM) from Psychosocial, Cultural and Reproductive Health Perspectives. This is considered important because psychosocial, cultural problems and lack of understanding of reproductive health are the drivers of early marriage. Education for PKK mothers, youth and youth organizations has succeeded in increasing perceptions of the negative impact of early marriage. Education participants also made an agreement to jointly reduce the number of early marriages by involving youth in Karang Taruna activities.